Pengaruh Metode Problem Based Learning (PBL) terhadap Hasil Belajar Siswa pada Mata Pelajaran Bahasa Inggris Kelas X SMK IT Al Qimmah - Saputra, Ari; Fikri, Zaenul (ANWARUL, 2022)
This study aims to determine the effect of the Problem Based Learning Method on Student Learning Outcomes in English Subject Class X SMK IT Al Qimmah academic year 2021/2022 . The method of learning English at SMKN 2 Selong is dominated by the old teaching method, namely the lecture method and giving assignments, this causes students to be passive and accept what is given by the teacher. Besides that, students are also not enthusiastic in the learning process and students prefer to be silent, so that communication only goes one way, therefore to solve this problem the researcher tries to use the Problem Based Learning Method on Student Learning Outcomes in English Class X SMK IT Al Qimmah Academic Year 2021/2022. This research is an experimental study with the research subjects used are students of class X.A as the experimental group with a total of 27 students and class X.B as a control group with a total of 27 students. After collecting and processing data, the researcher got the average score for the experimental group, which was 85.18, while in the control group it was 71.56. In testing the hypothesis, the researcher used the t-test formula. The researcher found that the t-test value was 4.276 and the t-table was at a significant level of 5%, namely 1.684, so the hypothesis was accepted. This means that there is an effect of the Problem Based Learning Method on Student Learning Outcomes in Class X English Subjects at SMK IT Al Qimmah academic year 2021/2022.